EFISIENSI PEMASARAN CABAI MERAH DI KECAMATAN ADILUWIH KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Ariep Budi Prayitno; Ali Ibrahim Hasyim; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research aims to find out marketing efficiency of red chili in Pringsewu District Lampung Province.Research site were selected deliberately. Sampling is done by following the line of marketing. This researchuses primary data and secondary data about. This research analyzed by marketing efficiency consist tochannel analysis, producers share, marketing margin and Profit Margin Ratio (PMR), price correlationanalysis, and elasticity of price transmission. The results showed that marketing system of red chili inPringsewu district is efficient. It is seen from the producers share of greater than 70 percent, althoughmarket structure of red chili in Pringsewu district is imperfectly competitive market (oligopsoni), thevariability market of red chili in Pringsewu district there are three marketing channels, profit margin ratio(PMR) at marketing of red chili is not prevalent, and then the value of elasticity price transmission of redchili in Pringsewu district is more than one.